2009
DOI: 10.1159/000228571
|View full text |Cite
|
Sign up to set email alerts
|

Management of Inflammatory Bowel Diseases during Pregnancy

Abstract: Inflammatory bowel diseases (IBD) have a high prevalence in younger patients with child-bearing potential. Usually, pregnancies in women with IBD will develop normally, if the patient is in remission or has minor disease activity at the time of conception. In contrast, the frequency of normal pregnancies is significantly reduced and the frequency of adverse outcomes like preterm birth or miscarriage is increased, when conception occurs in phases with active IBD. Therefore, it is generally recommended to women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Neither the diagnosis of IBD nor the adequate medical therapy are medical indications for abortion. 33,[70][71][72][73][74] The basic principles of the medical IBD therapy before and during pregnancy are: (i) An acute flare has to be treated prompt and effectively. (ii) An effective therapy should not be discontinued, if not contraindicated.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the diagnosis of IBD nor the adequate medical therapy are medical indications for abortion. 33,[70][71][72][73][74] The basic principles of the medical IBD therapy before and during pregnancy are: (i) An acute flare has to be treated prompt and effectively. (ii) An effective therapy should not be discontinued, if not contraindicated.…”
Section: Therapymentioning
confidence: 99%
“…The risk for pre‐term birth and small for gestational age neonates under this medication is increased. Neither the diagnosis of IBD nor the adequate medical therapy are medical indications for abortion …”
Section: Therapymentioning
confidence: 99%
“…[83] It has been demonstrated that various patient factors can influence the pharmacokinetic parameters of systemic tacrolimus, which include demographic characteristics, [84][85][86][87] hepatic dysfunction, [84,85,88] hepatitis C, renal function, time after transplant, age, donor characteristics, sex, race, hematocrit and albumin concentrations, diurnal variations, administration of food, corticosteroid dosage, diarrhea, ascites, short or absent small bowel jejunostomy, and intestinal P-glycoprotein as well as cytochrome P450 expression. [53] Orally administered tacrolimus is also used for treatment of rheumatoid arthritis, [89][90][91] moderate to severe psoriasis, [92,93] and inflammatory bowel disease, [94][95][96][97] often in combination with other therapeutics. Lower daily doses (1.5-3 mg day) than for transplant patients are used for these conditions, resulting in lower trough tacrolimus concentrations in serum ranging from 2 to 10 ng mL.…”
Section: Gvhd Unknownmentioning
confidence: 99%
“…Furthermore, the risk of spontaneous abortions and fetal abnormalities are not significantly increased with basic IBD medications. 17 However, there is an increased risk of preterm births and reduced weight at birth; 17 there is no indication for therapeutic abortion. 18 Active IBD can be treated with 5-ASA derivatives, budesonide, and corticosteroids as in non-pregnant patients.…”
Section: Medical Management Of Inflammatory Bowel Disease During Preg...mentioning
confidence: 99%